Takayasu Arteritis Diagnosed by Carotid artery Doppler: A Rare Case Report (Bangladesh Journal of Radiology and Imaging, 2026)
Takayasu arteritis is a rare, granulomatous large vessel vasculitis which is also known as “Pulseless disease” or “Martorell syndrome”. Chronic inflammation leads to stenosis, occlusion and aneurysm of vessels. Here we present a case of a 40years old male patient diagnosed as Type-I Takayasu arteritis using carotid doppler and confirmed by CT angiography.